2019
DOI: 10.1038/s41583-019-0126-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuron–glia interactions in the pathophysiology of epilepsy

Abstract: Epilepsy is a neurological disorder afflicting ~65 million people worldwide. It is caused by aberrant synchronized firing of populations of neurons primarily due to imbalance between excitatory and inhibitory neurotransmission. Hence, the historical focus of epilepsy research has been neurocentric. However, the past two decades have enjoyed an explosion of research into the role of glia in supporting and modulating neuronal activity, providing compelling evidence of glial involvement in the pathophysiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
296
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(314 citation statements)
references
References 147 publications
9
296
1
8
Order By: Relevance
“…Interestingly, pathogenic mutations in RORB have been identified in genetic forms of epilepsy (Rudolf et al, 2016). Since astrocyte dysfunction is considered a key pathological mechanism in epilepsy (Patel et al, 2019), these RORB mutations may act by blocking the induction of mature astrocyte genes protecting from epileptogenesis (Patel et al, 2019), such as the Rorb target Glul, whose deletion in astrocytes in the mouse causes seizures and neurodegeneration (Zhou et al, 2019), or the glutamate transporter Slc1a2, which has been shown to be mutated in epileptic encephalopathies (Epi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pathogenic mutations in RORB have been identified in genetic forms of epilepsy (Rudolf et al, 2016). Since astrocyte dysfunction is considered a key pathological mechanism in epilepsy (Patel et al, 2019), these RORB mutations may act by blocking the induction of mature astrocyte genes protecting from epileptogenesis (Patel et al, 2019), such as the Rorb target Glul, whose deletion in astrocytes in the mouse causes seizures and neurodegeneration (Zhou et al, 2019), or the glutamate transporter Slc1a2, which has been shown to be mutated in epileptic encephalopathies (Epi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Excess glutamate release and xCT expression. Elevated extracellular glutamate is a key contributor to cortical hyperexcitability, SD, epileptiform activity, and excitotoxicity (26,33). Although a principal role of glia in glutamate homeostasis involves extracellular glutamate uptake via Glut1-mediated transport, astrocytes also regulate extracellular glutamate release via the cysteine/glutamate antiporter system xc-.…”
Section: Pathogenesis Of Peritumoral Hyperexcitability In An Immunocomentioning
confidence: 99%
“…Astrocytes, as the most numerous glial cells in the CNS, play many essential roles in tissue homeostasis, synaptic transmission, and neuroimmune responses (Farina et al, 2007;Clarke and Barres, 2013). Accumulating compelling evidence suggests that aberrant astrocyte activation contributes to the pathophysiology of epilepsy (De Lanerolle et al, 2010;Yin et al, 2015;Patel et al, 2019). Together with epidemiological evidence that systemic inflammation increases an individuals' susceptibility to seizures by lowering their seizure threshold (Yuen et al, 2018), these studies provide the foundation for the hypothesis that inflammation is a critical modulator of brain excitability.…”
Section: Prenatal Insultsmentioning
confidence: 99%